2016
DOI: 10.3892/ol.2016.5288
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin induces HepG2 cell cycle arrest through targeting specific long noncoding RNAs and the p53 signaling pathway

Abstract: Cisplatin has been used effectively in the treatment of hepatocellular carcinoma (HCC). Long noncoding RNAs (lncRNAs) were recently reported to contribute to the pathogenesis and progression of HCC. Their molecular mechanism related to cisplatin treatment remains unclear. The purpose of this study is to identify specific lncRNAs and to clarify their functions in HCC after cisplatin exposure. Reannotation and identification of differentially expressed lncRNAs were performed using the microarray data set GSE3812… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 42 publications
3
21
1
Order By: Relevance
“…Wang et al reported that the expression level of lncRNA RP11-363E7.4 was elevated in cisplatin-treated HepG2 cells as assessed by microarray analyses, and finally confirmed with qPCR. Further experiments showed that lncRNA RP11-363E7.4 positively regulated CDKN1A, TP53I3 and PPM1D at the gene level [52]. In our study, we confirmed with qPCR that lncRNA RP-11363E7.4 had decreased expression in five GC tissues.…”
Section: Discussionsupporting
confidence: 77%
“…Wang et al reported that the expression level of lncRNA RP11-363E7.4 was elevated in cisplatin-treated HepG2 cells as assessed by microarray analyses, and finally confirmed with qPCR. Further experiments showed that lncRNA RP11-363E7.4 positively regulated CDKN1A, TP53I3 and PPM1D at the gene level [52]. In our study, we confirmed with qPCR that lncRNA RP-11363E7.4 had decreased expression in five GC tissues.…”
Section: Discussionsupporting
confidence: 77%
“…It has been reported to be dysregulated in papillary thyroid carcinoma, in hepatocellular carcinoma after cisplatin exposure, and in patients with atrial fibrillation and myocardial infarction. [17][18][19][20] As previously reported, it was downregulated in GC tissues according to the tissue microarrays results, while high expression of lncRNA RP11-363E7. 4 was associated with better overall survival in GC patients.…”
Section: Introductionsupporting
confidence: 74%
“…It was demonstrated that the most frequently identified mutations in HCC led to inactivation of p53. Cisplatin has been effectively used in the treatment of HCC, and p53 signaling is a potential target of cisplatin treatment (27). Paired box 5 (PAX5) has been suggested to be a functional tumor suppressor involved in HCC through direct regulation of the p53 signaling pathway, and Ras association domain family member 10 has been demonstrated to suppress human HCC growth by activating p53 signaling (28,29).…”
Section: Discussionmentioning
confidence: 99%